Acute Hydrocephalus due to Secondary Leptomeningeal Dissemination of an Anaplastic Oligodendroglioma - Andreas M. Stark; Heinz-Herrmann Hugo; H. Maximilian Mehdorn; Friederike Knerlich-Lukoschus (Case Reports in Medicine)
Secondary leptomeningeal dissemination of oligodendroglioma is very rare. We report the case of a 38-year-old Caucasian male who presented with acute hydrocephalus. 8 months before, the patient had undergone craniotomy for right frontal anaplastic oligodendroglioma, WHO grade III. By that time, there was no evidence of tumor dissemination. MRI now ruled out local tumor progression but revealed meningeal contrast enhancement along the medulla, the myelon, and the cauda equina. Repeated lumbar puncture revealed increased cerebro-spinal fluid (CSF) pressure and protein content. Malignant cells were not detectable. Surgical treatment consisted in (1) placement of an ommaya reservoir for daily CSF puncture, (2) Spinal dural biopsy confirming leptomeningeal oligodendroglioma metastasis, and (3) ventriculo-peritoneal shunt placement after CSF protein has decreased to 1500–2000 mg/l.